Temperature, pressure, and humidity SAW sensor based on coplanar integrated LGS - Liang, Xiaorui (2023)
This paper presents a surface acoustic wave (SAW) sensor based on coplanar integrated Langasite (LGS) that is fabricated using wet etching, high-temperature bonding, and ion beam etching (IBE) processes. The miniaturized multiparameter temperature‒pressure-humidity (TPH) sensor used the MXene@MoS2@Go (MMG) composite to widen the humidity detection range and improve the humidity sensitivity, including a fast response time (3.18 s) and recovery time (0.94 s). The TPH sensor was shown to operate steadily between 25-700 °C, 0-700 kPa, and 10-98% RH. Coupling issues among multiple parameters in complex environments were addressed by decoupling the Δf-temperature coupling factor to improve the accuracy. Therefore, this work can be applied to simultaneous measurements of several environmental parameters in challenging conditions.